Implementation of the Empowerment Program for Culinary Tourism Business Actors in the Coastal Area of Manado Bay, North Sulawesi Province - Lengkong, Florence D. J.; Londa, Very Y.; Plangiten, Novva N.; Palar, Novie R. A. (Journal La Bisecoman, 2024)
The Manado City Government through the 2020-2025 regional tourism development master plan has determined a special tourism destination cluster for culinary tourism areas with urban-coastal tourism attractions. The determination of this cluster is in line with the culinary potential managed by the community such as bakat sea fish and local snacks around the coast of Manado Bay. By using a qualitative research design, data was collected directly at the research location through interviews and observations, and secondary data was also collected electronically through internet media such as Google Scholar, WoS databases, Scopus, Arxiv by Cornell, Ulrich's Web, Science Direct, Directory of Open Access, JSTOR, SciELO, ERIC, ResearchGate and others. Data analysis using an interactive analysis model with data reduction, data display and conclusion drawing/verification stages. In addition, for the validity of the data analysis discussion, a focus group discussion was also conducted. The research findings that the implementation of the empowerment program for culinary tourism entrepreneurs in the Manado Bay Coastal Area has been carried out by the Manado City Government. Training, mentoring, provision of capital and business facilities and supervision as a form of empowerment activities carried out. The empowerment program is carried out separately or in collaboration with other public organizations. The seriousness in managing and developing businesses from the Community is a measure of the success of the implementation of the empowerment program.